2020
DOI: 10.1007/s10389-020-01395-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent perspectives and awareness on transmission, clinical manifestation, quarantine measures, prevention and treatment of COVID-19 among people living in Malaysia in 2020

Abstract: Background There is a major public health challenge threatening the world with the rapid spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which emerged in December 2019 from Wuhan, China. Objective The aim of this study was to assess the knowledge, attitude and practice regarding COVID-19 and its transmission, causes and prevention among people living in Malaysia. Methods A cross-sectional study was conducted among people living in Malaysia by using an online survey in March and April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This study resulted that the health-seeking behaviour among educated young adults was significantly related to education background; education level and courses. This correlated with a previous study in Malaysia, that shows educated people had positive health-seeking behaviours and associate with good knowledge about the COVID-19 pandemic (22,47) new norm of ODL that may become a stress factor to them. The planning of reopening of higher education institutions should be prepared with strict SOP based on guidelines by the World Health Organization (WHO) to prevent the COVID-19 transmission.…”
Section: Vi) Stress Level During Covid-19 Pandemicsupporting
confidence: 89%
“…This study resulted that the health-seeking behaviour among educated young adults was significantly related to education background; education level and courses. This correlated with a previous study in Malaysia, that shows educated people had positive health-seeking behaviours and associate with good knowledge about the COVID-19 pandemic (22,47) new norm of ODL that may become a stress factor to them. The planning of reopening of higher education institutions should be prepared with strict SOP based on guidelines by the World Health Organization (WHO) to prevent the COVID-19 transmission.…”
Section: Vi) Stress Level During Covid-19 Pandemicsupporting
confidence: 89%
“…In addition, the high Rt observed during the Sri Petaling mass gathering could also be attributed due to the event occur early on in the pandemic, whereby there was a lack of awareness among the public regarding COVID-19 resulting in poor compliance to SOPs (i.e. use of face mask, regular hand hygiene and physical distancing) 37 . Compared to the Sri Petaling event, the Rt during the Sabah electoral process was lower, as this mass gathering event did not occur in a confined area and consisted of multiple propagated small events occurring in open areas out over a longer period.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors contributed to the high level of knowledge among our cohort. Previous studies on COVID-19 knowledge have shown that female respondents generally displayed greater scores in comparison to their male counterparts [ 15 , 17 , 18 , 19 ]. Higher education level is a positive predictor of adequate knowledge on COVID-19, as shown by various population studies [ 17 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%